Glucokinase as an emerging anti-diabetes target and recent progress in the development of its agonists - Yixin Ren; Li Li; Li Wan; Yan Huang; Shuang Cao (Taylor & Francis Group, 2022)
Type 2 diabetes mellitus is a metabolic disorder with complicated pathogenesis, and mono-target therapy often fails to effectively manage the levels of blood glucose. In recent years, the anti-diabetes target glucokinase (GK) has attracted the attention of researchers. It acts as a glucose sensor, triggering counter regulatory responses following a change in glucose levels to aid restoration of normoglycemia. Activation of GK induces glucose metabolism and reduces glucose levels for the treatment of type 2 diabetes. GK agonists (GKA) are a new class of antidiabetic drugs. Among these agents, dorzagliatin is currently being investigated in phase III clinical trials, while PB-201 and AZD-1656 have reached phase II clinical trials. This article describes the mechanism of action of GK in diabetes and of action of GKA at the protein level, and provides a review of the research, trends, and prospects regarding the use of GKA in this setting.